Factors Associated with Depression among Prisoners in Women’s Class II-A Prison Jakarta - Juliane, Zhara; Machmud, Putri Bungsu (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Depression is a common mental disorder, characterized by persistent sadness and a loss of interest in activities that you normally enjoy, accompanied by an inability to carry out daily activities, for at least two weeks. Female prisoners represent groups at risk of depression where depression in prisoners is more vulnerable to female prisoners than men. This study aims to determine the factors associated with depression among prisoners in Women’s Class II-A Prison Jakarta. The study design used was cross-sectional with multivariate analysis, multiple logistic regression. The number of research samples is 200 prisoners taken using random sampling techniques. The results showed that the prevalence of depression among prisoners in Women’s Class II-A Prison Jakarta is 56,5%. Based on the results of the multivariate analysis, it can be seen that factors related significantly to depression are age (p-value = 0.012; POR = 2.144; 95% CI = 1.185 - 3.879) and recidivism status (p-value = 0.043; POR = 3.926; 95% CI = 1,047 –14,729) which the most influential factor on the incidence of depression is recidivism status. Government attention needs to be given to the mental health of prisoners by conducting various mental health programs and services such as regular screening and rehabilitation programs.